1987
DOI: 10.1017/s002211208700260x
|View full text |Cite
|
Sign up to set email alerts
|

The lift force on a spherical body in a rotational flow

Abstract: This paper concerns the flow about a sphere placed in a weak shear flow of an inviscid fluid. The secondary velocity resulting from advection of vorticity by the irrotational component of the flow is computed on the sphere surface, and on the upstream axis. The resulting lift force on the sphere is evaluated, and the result is confirmed by an analytical far-field calculation. The displacement of the stagnation streamline, far upstream of the sphere, is calculated more accurately than in previous papers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
268
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(284 citation statements)
references
References 5 publications
14
268
1
1
Order By: Relevance
“…The bubbles are tracked by solving the following dynamical equation in which their mass is neglected (see, e.g., [13]): in which C A = 1/2 and C L = 1/2 are the added mass and lift coefficients, respectively [14,15]. The drag coefficient is modeled as mentioned in [16,17] as follows:…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…The bubbles are tracked by solving the following dynamical equation in which their mass is neglected (see, e.g., [13]): in which C A = 1/2 and C L = 1/2 are the added mass and lift coefficients, respectively [14,15]. The drag coefficient is modeled as mentioned in [16,17] as follows:…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…Auton (1987) showed that (for incompressible/inviscid fluid) the acceleration experienced by the particle is proportional to the velocity gradient du/dy and the slip velocity, the latter being a function of the particle size. Larger particles have a longer response time and will experience larger slip velocities.…”
Section: Particle Image Velocimetrymentioning
confidence: 99%
“…In the sediment transport literature, except, notably, the paper by Madsen [1991], this term usually has been ambiguously, if not incorrectly, given as dU i /dt. Maxey and Riley [1983] and Auton [1987] have pointed out the importance of distinguishing between the derivative following the geometric center of the sediment particle and the derivative following the fluid at the position of the geometric center in the reference flow. Although for low particle Reynolds number R p the error is not large, for high R p it is substantial [Maxey and Riley, 1983;Mei et al, 1991].…”
Section: A1 Equation Of Motionmentioning
confidence: 99%